A Simplified Scoring System for Diagnosing Allergic Rhinitis in Indonesian Primary Care Settings: A Cross-Sectional Study Comparing Accuracy to Specialist Diagnosis - Febria Suryani; Irna Nettles; Aisyah Andina Rasyid; Fifia Ardinanti (Phlox Institute: Indonesian Medical Research Organization, 2025)
Introduction: Allergic rhinitis (AR) is a prevalent condition in Indonesia, yet often underdiagnosed and undertreated in primary care settings. Access to specialist otorhinolaryngologists is limited, particularly in rural areas. A simplified, accurate diagnostic tool for primary care physicians (PCPs) could significantly improve early diagnosis and management. This study aimed to develop and validate a simplified scoring system for AR diagnosis in Indonesian primary care, comparing its accuracy to the gold standard of specialist diagnosis. Methods: A cross-sectional study was conducted in five major Indonesian cities (Medan, Palembang, Jakarta, Surabaya, and Makassar) across various primary care clinics. Patients presenting with nasal symptoms suggestive of AR were recruited. Each patient was assessed by a PCP using the newly developed